Arthroprosthetic cobaltism and pseudotumour also occur in patients with small diameter femoral ball head metal-on-metal total hip arthroplasties. (28th March 2014) - Roessler, Philip P; Witt, Florian; Efe, Turgay; Schmitt, Jan
Abstract : Metal-on-metal implants have been widely discredited in public during the past few months. At the same time patients' awareness has risen leading to an increased number of consultations regarding the topic. As hip resurfacings and total hip arthroplasties with large diameter femoral ball heads are already known for excessive metal wear, even small diameter ball heads with low friction get into focus now. We report a case of a 75-year-old man with recurrent hip pain almost 14 years after low friction metal-on-metal total hip arthroplasty. In addition to elevated serum cobalt levels, a type IV sensitivity reaction to cobalt could be noted. Explantation of a highly worn small diameter femoral ball head as well as development of the so-called pseudotumour indicate that all patients should be screened for signs of metal wear regardless of their specific risk factors or the type of metal-on-metal implant.